Foreign Women Transforming Elijah into the Prophet of the Lord (1 Kgs 17–19) - Dubovský, Peter (The Biblical Annals, 2024)
This paper analyses the different versions of the Elijah cycle (1 Kgs 17–19) as witnessed, in particular, in the Masoretic text (MT), the Codex Vaticanus (GB), the Codex Alexandrinus (GA), and the Antiochian text (GAnt.). The comparison of the manuscripts shows that the MT adds and omits certain words and expressions. The author explored whether the additions and omissions are scribal mistakes or rather an intentional redactional intervention. Arguing for the latter, the author proposes that the MT presents not only the great deeds of the great prophet Elijah but also how Elijah became such a great prophet. Based on this analysis, the author proposes five stages of Elijah’s formation process: 1 . t he transformation of a man into a listener (1 Kgs 17:2–6); 2. Elijah’s transformation into a man of God’s word (the Cherith episode and the Zarephath episode in 17:7–16); 3. the transformation from a man of God’s word into a man of God (the resuscitation of the dead son in 17:17–24); 4. the transformation from a man of God into a prophet (the Carmel episode 18:1–40); 5. the transformation of a zealous prophet into a man standing before the Lord (19:1–18).